COMPUTER GRAPHICS AND HOW THINGS WORK IN WORLD AROUND US - BERNAT, Milan; BERNATOVA, Renata (Journal of Technology and Information Education, 2011)
The paper reports the aspects related to Java applets creation and their application in teaching technical and natural subjects. The authors of the paper also present the Java applets he himself created and applied in the natural and technical teaching process. At the same time he emphasises the irreplaceability of didactic and professional mastership of a teacher in the teaching process using Java applet programs.
Keywords: computer; teaching technical and natural subjects